Learning to pay by phone: MOBIS, Ensibuuko's mobile-money app in Uganda - Otim, Gerald; Tokwiny, Alfred (Technical Centre for Agricultural and Rural Cooperation, 2017)
Ensibuuko provides a mobile banking app called MOBIS to its clients: rural savings and credit cooperatives. It taught members of these cooperatives how to the app, so boosting client uptake.